Evaluation of thermal reaction for two azo compounds by using 20-L apparatus and calorimetry. (November 2021) - Lin, Kuei-Hua; Lin, Wei-Cheng; Liu, Shang-Hao; Shu, Chi-Min
Abstract: Azo compounds are widely involved in the industrial processes of dyes, pigments, initiators, and blowing agents. Unfortunately, these compounds have a bivalent unstable –NN– composition, which can be readily broken when the ambient temperature is elevated. Self-accelerating decomposition might cause a runaway reaction and lead to a fire, explosion, or leakage when the cooling system fails or other events occur. This study investigated the explosion properties, thermal stability parameters, and thermal hazard and mechanism of 2, 2′–azobisisobutyronitrile (AIBN) and 2, 2′–azobis–2–methylbutyronitrile (AMBN). We used a 20-L apparatus, vent sizing package 2, synchronous thermal analysis, and differential scanning calorimetry under explosive, adiabatic, and dynamic conditions to acquire the explosive curves, thermal curves, and thermodynamic parameters of the substances. Moreover, the differential isoconversional method (Friedman method) and ASTM E698 equation were employed to obtain the apparent activation energy E a . All the experimental results revealed that AIBN is more dangerous than AMBN. The E a of AIBN was lower than that of AMBN. The results can be used to construct an azo compound thermal hazard database for use for searches and reference examples by industry and related research areas. Highlights: Thermal stability parameters and explosion properties of AIBN were both more dangerous than AMBN's. There was only one stage on mass loss using AIBN, whereas there were two periods using AMBN. E a of AMBN were greater than AIBN which means AIBN is more dangerous than AMBN.